Current situation, bottlenecks, and path options for the development of capital flows and integration in the Yangtze River Delta region - Yang, Jing; Li, Guofan; Zhong, Zhuowen; Li, Qiang; Du, Guolei; Guo, Jinhan (Frontiers in Sustainable Cities, 2023)
Only the effective flow of capital factors can help to improve the efficiency of resource allocation and promote the development of integrated capital market. Therefore, based on the connotation analysis of capital and its flow, capital market integration and other concepts, this paper constructs indicators in terms of social fixed asset investment, bank capital flow, government transfer payments, social financing structure, foreign direct investment, etc., deeply analyzes the current situation and bottlenecks of the development of capital flow and integration in the Yangtze River Delta region, further summarizes and draws on foreign experience in the development of capital flow and integration, and proposes The study further summarizes and draws lessons from foreign experiences in capital flow and integration development, and proposes path options for the development of capital flow and integration in Yangtze River Delta region. The conclusion of the study shows that the main existing bottlenecks of listed companies, the existing bank management system is not sound, and the government competition and administrative barriers coexist, and suggests path options such as promoting the development of listed companies, sound bank management model, improving relevant government policies and optimizing the investment environment.